Recent developments in technology for the assessment and management of incontinence. (3rd October 2015) - Hillary, Christopher J.; Slovak, Martin; McCarthy, Avril; Hashim, Hashim; Chapple, Christopher R.
Abstract: Urinary incontinence, the leakage of urine, is a common condition, which can have a significant impact on a patient's quality-of-life. Incontinence may arise as a consequence of a weakness of the urinary sphincter or bladder dysfunction, usually over-activity. Incontinence therapies occupy a large proportion of the healthcare budget. As no single device to manage incontinence is appropriate for all situations, a diverse range of products are available on the market and the development of improved products based on fundamental designs has been slow. This review highlights some of the key issues of continence care and describes the current technology and recent developments involved in the diagnosis, assessment and treatment of incontinence, along with the strengths and limitations of these methods. These issues are imperative to address if improved technology is to be developed.